Implementation of automation controller using electro-pneumatic & PLC for food processing - Nasita, Ibrahim (2006)
This project describes a design and Implementation of Automation Controller using Electro pneumatic and PLC for food processing. The proposed model system is designed based of the usage of pneumatic, electro pneumatic and Programmable Logic Controller (PLC). This project is focus to small medium industry (SMI). SMI is defined as manufacturing companies or companies providing manufacturing related services with annual sales turnover not exceeding RM25inillion and with fulltime employees not exceeding 150. The aim of this project is automating the processing food in the industry that still using manual system. It because many industry nowadays using automation machine in processing their production. Automation machine can gives more advantages to the industry such as it can improve quality and accuracy of the product, increase productivity and also tremendous amounts of power and energy which humans do not possess will be decrease by using automatic machines like electro-pneumatic and PLC. The electropneumatic and PLC design will be proposed to that process in prototype model. This system can be applied in industry factories that are developed to automatic system.